BUSINESS TRANSFORMATION OF ARAB DESCENT IN PONTIANAK CITY - Alwi Al Attas; Luqman; Yulia (I-Economics: A Research Journal on Islamic Economics)
This study aims to find out the process of business change of Arab descendants in Pontianak City and find out what factors cause business changes of Arab descent in the city of Pontianak. The subject of this research is Ngabuleh students. The type of research is qualitative. The data collection technique used interview techniques, non-participant observation and documentation. Data analysis with steps, namely data reduction, data display, conclusion and verification. Data validity techniques using triangulation and member check. The results of this study conclude: The business transformation of Arabs in the city of Pontianak has undergone a significant transformation over time. Initially, they were involved in the trade of spices, textiles, and jewelry, as well as opening small businesses in traditional markets. Now, they have expanded into the property, hospitality, education, healthcare, culinary, and e-commerce sectors. The driving factors for this change include globalization, technological advancements, changes in people's lifestyles, and dynamic market demands. Technology plays a crucial role in business transformation, with the application of digital systems for operational management, marketing, and financial transactions. In addition, market development strategies are now more open, leading to expansion into other major cities and penetration of the digital market. The factors that cause the change in business of Arab descent in Pontianak City prioritize the values of honesty, integrity, and family, although adopting the values of innovation and professionalism to adapt to the changing times and technology. Formal education and field experience complement each other in shaping the way of doing business, while changing demographics and technology are forcing businesses to innovate, especially in the face of online consumption trends. Increasingly fierce competition and government policies that support small businesses are important factors, along with the influence of digital lifestyles and Arab culture that emphasize long-term relationships. Macro and microeconomic conditions and economic crises, such as in 1997, teach the importance of product diversification and operational efficiency. The development of information technology has also made it easier for businesses to interact, although the cost and training challenges of employees need to be faced